2007
DOI: 10.1097/ijg.0b013e31802ff85f
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Office Intraocular Pressure and 24-hour Intraocular Pressure in Patients With Primary Open-angle Glaucoma Treated With a Combination of Topical Antiglaucoma Eye Drops

Abstract: In POAG patients treated with 3 kinds of antiglaucoma eye drops, office IOP was similar to mean 24-hour IOP. However, it was difficult to estimate 24-hour IOP fluctuation and maximum 24-hour IOP on the basis of office IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 23 publications
4
39
0
1
Order By: Relevance
“…Barkana et al [24] highlighted that current standards do not identify nearly 70% of peak IOP and underestimate fluctuations by a mean of 3 mm Hg. Similar results were obtained in other studies showing IOP peaking outside office hours in 52-66% of cases [25,26,27,28]. In our study, we showed that the collection of a large number of measurements can clarify the characteristics of IOP in most cases, highlighting the correlation between these parameters.…”
Section: Discussionsupporting
confidence: 78%
“…Barkana et al [24] highlighted that current standards do not identify nearly 70% of peak IOP and underestimate fluctuations by a mean of 3 mm Hg. Similar results were obtained in other studies showing IOP peaking outside office hours in 52-66% of cases [25,26,27,28]. In our study, we showed that the collection of a large number of measurements can clarify the characteristics of IOP in most cases, highlighting the correlation between these parameters.…”
Section: Discussionsupporting
confidence: 78%
“…Nakakura et al 87 also investigated the relation between office and 24-hour IOP characteristics in 71 treated eyes of 42 POAG patients. Office IOP was derived from three outpatient measurements (9 AM to 6 PM) during a six-month period with the same treatment.…”
Section: Circadian Iop Variations In Treated Eyesmentioning
confidence: 99%
“…We suspect that this disparity may be due to measurement of daytime IOP only and that maximum and minimum IOP may have changed outside of daytime hours in the earlier study. 7,8 is that the earlier investigators included both eyes in their study, which may have led to a TNR double-counting error. Additionally, 96% of their patients were Caucasians.…”
Section: Discussionmentioning
confidence: 99%